'Globalist war against humanity shifts into high gear': Online anti-vaccination websites and 'anti-public' discourse. (April 2019) - Davis, Mark
Online media has provided unprecedented opportunities for anti-vaccination groups to spread their message. An extensive scholarly literature has consequently emerged to analyse such discourse and develop strategies for countering it. In this article, I take a different approach. My contention is that it is no longer appropriate to approach anti-vaccination discourse as a stand-alone formation. Such sites, I argue, building on work by McKenzie Wark and Bart Cammaerts, are increasingly part of a wider proliferation of 'anti-public' discourse that contests fundamental democratic conventions, rules of argumentation and so on. The article uses a mixed methods approach based on a systematic content survey supplemented by the presentation of qualitative examples from 56 anti-vaccination websites. By locating anti-vaccination discourse in these broader contexts, I argue, it is possible to understand it as related to a more general transformation in public deliberation.